Assessment of freeze-thaw erosion by retrogressive thaw slump on the Qinghai-Tibet Plateau combined with geophysical methods - Chenglong Jiao; Fujun Niu; Peifeng He; Jing Luo; Fan Yu (npj Natural Hazards)
Abstract Retrogressive thaw slumps (RTSs) are significant thermokarst features in alpine permafrost environments of Arctic regions and the Tibetan Plateau (QTP), China. These formations contribute substantially to freeze-thaw erosion and organic carbon release, affecting regional ecological dynamics. Despite their importance, geophysical evidence of freeze-thaw erosion in RTS development areas remains limited due to challenging access and insufficient multi-methodological analyses. This study presents a high-resolution geophysical investigation of RTS development in the Beiluhe River Basin, QTP. Using a multi-methodological approach, we quantitatively assess freeze-thaw erosion processes by characterizing lithostratigraphy, ground ice distribution, hydrogeological properties, and deformation patterns across the RTS. Our findings reveal that freeze-thaw processes and lateral thermal erosion from the headwall create significant heterogeneity in soil hydraulic properties along the development direction, with an estimated total volume change of approximately 13,139 m³ in the studied area. These insights illuminate the complex freeze-thaw processes driving RTS development and their ecological implications across the QTP.